Total Plate Number and Organoleptic Tests of Yellow Lellar Fish (Selaroides leptolepis) - Saud, Royke Gilbert Saud; Reo, Albert Royke; Sanger, Grace; Montolalu, Lita. A.D.Y.; Taher, Nurmeilita; Palenewen, Joyce C. V. (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2024)
The aim of this research is: To determine the quality of yellowtail trevally fish sold in the Boulevard area of ​​Manado City. The research method used in this research is the Descriptive method with observation parameters consisting of counting the number of bacterial colonies using the Total Plate Number (ALT) Method and Organoleptic quality (sensory assessment), regarding the appearance of the eyes, mucus, flesh, and tektite. Sampling was carried out in the morning (A) and afternoon (B) with 2 (two) repetitions. The panelists used are semi-trained panelists. The sample size in this study was 6 yellow trevally fish at each sample collection time (A and B) for 26 panelists. Based on the research results, the average Total Plate Number (ALT) in the morning and afternoon was as follows: 5.65 ×10^3 and 4.15 ×10^3, it was concluded that the quality of the fish was good, fresh, and suitable for consumption. The results of research on organoleptics regarding eyes, gills, mucus, meat, and texture obtained average values ​​ranging from 8.3 to 9.0. These results show that the yellow trevally fish is still fresh and suitable for consumption. Based on the results of this research, through an assessment of the ALT and organoleptic values, it can be concluded that the quality of the yellow trevally marketed in the Boulevard area is suitable for consumption according to SNI standards. Keywords: Yellow trevally, ALT, and organoleptic Abstrak Tujuan dari penelitian ini adalah:  Mengetahui kualitas ikan selar ekor kuning yang dijual di Kawasan Boulevar Kota manado.   Metode penelitian yang di gunakana dalam penelitian ini adalah metode Deskriptif dengan parameter pengamatan  teridi dari menghitung jumlah koloni bakteri dengan Metoda  Angka Lempeng Total (ALT) dan kwalitas Organoleptik (penilaian secara sensorik), terhadap penampakan  mata, lendir, daging dan tektir. Pengambilan sampel dilakukan pada pagi hari (A) dan diang Hari (B) dengan ulangan sebanyak 2 (dua) kali. Panelis yang digunakan adalah panelis semi terlatih. Besaran sampel pada penelitian ini yaitu 6 ekor ikan selar kuning pada masing-masing waktu pengambilan (A dan B) sampel untuk 26 orang panelis panelis. Berdasarkan hasil penelitian diperoleh Angka Lempeng Total (ALT) pada pagi dan siang rata-rata diperoleh  sebagai berikut: 5,65 ×10^3 dan 4,15  ×10^3 disimpulkan kualitas ikan baik, segar dan layak dikonsumsi.  Hasil penelitian tentang  organoleptik terhadap  mata, insang, lendir,  daging dan tektur diperoleh nilai nilai rata-rata berkisar 8,3 sampai 9,0. Hasil tersebut menjelaskan ikan selar kuning masih segar dan layak di konsumsi. Berdasarkan  hasil penelitian ini melalui penilaian terhadap nilai ALT dan organoleptik dapat disimpulkan bahwa  kualitas ikan selar kuning yang dipasarkan di Kawasan Boulevart layak dikonsumsi menurut standart SNI. Kata Kunci: Ikan selar kuning, ALT dan organoleptik